The Development of an Integrity Zone at the Office of the Ministry of Religious Affairs of Jember Regency: A Review of Management Functions from an Islamic Education Perspective Using the PDCA Approach - Faisol Abrari (Universitas Nurul Jadid, 2025)
This study aims to analyze the implementation of Integrity Zone (ZI) development toward Corruption-Free Areas (WBK) and Clean and Serving Bureaucratic Areas (WBBM) through a management function perspective based on the PDCA (Plan, Do, Check, Act) cycle at the Office of the Ministry of Religious Affairs in Jember Regency. The development of Integrity Zones often encounters challenges related to bureaucratic formalism, where implementation tends to focus on fulfilling administrative documents rather than achieving substantive transformation. Therefore, a systematic and sustainable management framework is required to ensure the effectiveness of bureaucratic reform. This research employed a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews with institutional leaders, the head of the ZI team, and coordinators of change areas. These data were further supported by direct observation and documentation studies of the ZI Evaluation Worksheet (LKE). Data analysis was conducted through data reduction, data display, and thematic conclusion drawing. The findings reveal that the success of Integrity Zone development is strongly supported by the consistent application of the PDCA cycle at every stage of management. In the planning phase (Plan), the organization formulates strategies based on actual needs. The implementation phase (Do) involves measurable bureaucratic reform programs. The evaluation phase (Check) ensures the achievement of performance indicators, while the action phase (Act) promotes continuous improvement. These findings indicate that the Integrity Zone is not merely an administrative instrument but has evolved into an organizational culture that emphasizes continuous improvement. Leadership plays a crucial role as a role model in internalizing integrity values, thereby fostering a clean, accountable, and service-oriented bureaucracy in a sustainable manner.